Simulator-Based Investigations of Human Error Potential with Railroad Automation in the Locomotive Cab. (September 2017) - Sebok, Angelia; Walters, Brett; Wickens, Christopher
Automation is being developed and implemented in a variety of industries with the goals of improving overall system performance and reducing the probability and impact of human or operator error. However, as automation is introduced, it changes the role of the operator and creates new opportunities for different and unanticipated types of errors. In the rail industry, automated safety protection and optimization systems are being introduced into the locomotive cab. This paper describes a simulator-based investigation of human-automation interaction in the locomotive cab. Three scenarios were conducted in a dynamic and realistic rail simulator with three professional locomotive engineers. This preliminary study identified three distinct errors related to failing to appropriately monitor automation, and suggested potential opportunities for design improvements.